A STRATEGY FOR DEVELOPING AND ENHANCING INTERDISCIPLINARY RESEARCH AND GRADUATE EDUCATION AT AIN SHAMS UNIVERSITY (ASU) - Khadri, Hanaa Ouda (European Scientific Journal, ESJ, 2014)
This paper provides a detailed Strategy for developing and enhancing interdisciplinary research and graduate education at Ain Shams University (ASU), Cairo, Egypt. However, in this study, the following research questions were put into consideration: How can interdisciplinary education and research flourish while maintaining strong backgrounds in the disciplines? How can universities lower or remove barriers to faculty participation in interdisciplinary education and research and create porous, flexible, less redundant environment that facilitates the flow of ideas, people and resources across disciplinary boundaries? What are the requirements for the establishment of interdisciplinary graduate programs?